Androgen deprivation therapy in high risk prostate cancer - Dams, Ritchell Van; Kishan, Amar U. (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
We thank Dr. Kim and colleagues for their interest in our study (1,2). The authors mention some limitations of our study, all of which were discussed in our initial report, but can be discussed further. First, however, it is worth noting that the central conclusion of the study is not necessarily that patients with Gleason grade group (GG) 5 tumors need lifelong androgen deprivation therapy (ADT), but rather that GG 5 tumors are not inherently resistant to ADT, as had been previously suggested (3).